Plexin-B3 Regulates Cellular Motility, Invasiveness, and Metastasis in Pancreatic Cancer - Saxena, Sugandha (Cancers (Basel), 2021)
SIMPLE SUMMARY: Plexins and their ligands Semaphorins are considered versatile regulators of cancer cell migration, angiogenesis, invasion, and metastasis. Previously our group identified Semaphorin-5A (SEMA5A), the ligand of Plexin-B3, involved in organ-specific homing of pancreatic cancer (PC) cells and plays a significant role in PC angiogenesis and metastasis. In this study, we delineate its receptor Plexin-B3 function and pathological expression in PC progression and metastasis. Our data demonstrate that impairment in the Plexin-B3 axis enhances cell motility and PC cells’ invasiveness, resulting in higher metastasis. Thus, SEMA5A/Plexin-B3 represents an attractive targetable axis in PC metastasis. ABSTRACT: The Plexins family of proteins are well-characterized transmembrane receptors of semaphorins, axon guidance cue molecules, that mediate the cell attraction or repelling effects for such cues. Plexins and their ligands are involved in numerous cellular activities, such as motility, invasion, and adhesion to the basement membrane. The detachment of cells and the gain in motility and invasion are hallmarks of the cancer metastasis cascade, thus generating interest in exploring the role of plexins in cancer metastasis. Semaphorin–plexin complexes can act as tumor promoters or suppressors, depending upon the cancer type, and are under investigation for therapeutic purposes. Our group has identified Semaphorin-5A (SEMA5A)/Plexin-B3 as an attractive targetable complex for pancreatic cancer (PC) metastasis. However, our understanding of the Plexin-B3 function and pathological expression in PC is limited, and our present study delineates the role of Plexin-B3 in PC malignancy. We examined the pathological expression of Plexin-B3 in PC tumors and metastasis using a human tissue microarray, disease progression model of PDX-Cre-Kras((G12D)) (KC) mice, and different metastatic sites obtained from the Kras(G12D); Trp53(R172H); Pdx1-Cre (KPC) mice model. We observed a higher Plexin-B3 expression in PC tumor cores than the normal pancreas, and different metastatic sites were positive for Plexin-B3 expression. However, in the KC mice model, the Plexin-B3 expression increased initially and then decreased with the disease progression. Next, to evaluate the functional role of Plexin-B3, we utilized T3M-4- and CD18/HPAF-Control and -Plexin B3 knockdown cells for different in vivo and in vitro studies. The knockdown of Plexin-B3 enhanced the in vitro cellular migration, invasiveness, and impaired colony formation in three-dimensional culture, along with an increase in cellular spread and remodeling of the actin filaments. We also observed a higher metastasis in nude mice injected with T3M-4- and CD18/HPAF-shPlexin-B3 cells compared to their respective control cells. Furthermore, we observed a lower number of proliferating Ki-67-positive cells and higher ALDH1-A1-positive cells in the tumors formed by Plexin-B3 knockdown cells compared to tumors formed by the control cells. Together, our data suggest that the loss of Plexin-B3 is associated with the interference of cell division machinery and the induction of stem cell-like characteristics in PC cells.